Shared Values of Certain Nonlinear Differential Polynomials of Meromorphic Functions (Communications in Mathematical Research, 2019)
In this paper, by using the idea of truncated counting functions of meromorphicfunctions, we deal with the problem of uniqueness of the meromorphic functionswhose certain nonlinear differential polynomials share one finite nonzero value.
Keywords: meromorphic function; shared value; differential polynomial; uniqueness